Psychological interventions for DBT-A suicide prevention with adolescents: a systematic review - de Luna Velasco, Laura Elena (2023)
Suicide is a public health problem, being a challenge, early detection and care from evidence-based models. Objective:To conduct a systematic review on the efficacy of dialectical-behavioral social-emotional skills training programs forsuicide prevention in students. The search was conducted in PUBMED, Web of Science, Taylor and Francis and PsycINFOdatabases, search period: 01/01/2011 to 04/05/23, keywords in Spanish and English: case study, experimental, experimental,clinical study, clinical studies, clinical trial, suicide, suicidal risk, suicidal attempt, suicidal ideation, suicidal behavior,suicide planning, suicidal thought, socioemotional, dialectical behavior therapy, behavior therapy, behavior therapy, thirdgeneration therapy, adolescent, teenager, teen, highschool students, secondary school student, middle school student, theselection strategy was P-Population, I-Intervention, Comparison-Intervention and R-Results. Results: four researches oninterventions using Dialectical Behavior Therapy for adolescents for the prevention of suicide risk were selected, theydescribe the efficacy of the intervention in the population of adolescents studied in clinical and educational contexts. Theyreported that the changes in the patients were maintained from one to two years and decreased hospital admissions, reductionof suicide risk and depressive symptomatology. More evidence and studies that conduct high quality randomized clinicaltrials with longer follow-up and adherence to the DBT model are needed. There is scarce evidence of universal and selectiveinterventions, implemented in educational contexts and guided by the methodological and theoretical principles of DBT foradolescents.